The Role of Grammar in Teaching Foreign Languages - Xikmatovna, Abdualimova Dilfuza; Dildora, Tillaxo’jayeva (Journal of Higher Education and Academic Advancement, 2024)
This article discusses the issues of communicative teaching of foreign languages based on communicative tasks. Communication-oriented education aims to teach communication in a foreign language using all necessary (not only communicative) tasks and methods.